A cardiac paraganglioma - Makotoko, M.; Plaatjies, R.A.; Swart, M.; Venter, J.H.A. (SA Heart Journal, 2017)
A 31-year-old man presented with a month’s history of severe headache, palpitations and excessive sweating. He had no prior illnesses and was not taking any medication. He was a non-smoker and a teetotaller. His parents had both died but he did not know the cause of their deaths.